2015
DOI: 10.1016/j.juro.2015.01.112
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Flexible Ureterorenoscopy for Solitary Renal Stones in the CROES URS Global Study

Abstract: Our data indicate that flexible ureterorenoscopy for a single intrarenal stone is a safe procedure. Best results after single session flexible ureterorenoscopy were obtained for stones less than 15 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 29 publications
5
35
1
3
Order By: Relevance
“…Therefore, we could not conclude that preoperative stenting increased postoperative fever rate, although an extended time of stenting may cause potential UTI (Shigemura et al, 2012). Also, the incidence of fever in our patients without preoperative stenting was similar with the results (3.6% for 10–20 mm renal stones) of CROES URS Global Study (Skolarikos et al, 2015). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, we could not conclude that preoperative stenting increased postoperative fever rate, although an extended time of stenting may cause potential UTI (Shigemura et al, 2012). Also, the incidence of fever in our patients without preoperative stenting was similar with the results (3.6% for 10–20 mm renal stones) of CROES URS Global Study (Skolarikos et al, 2015). …”
Section: Discussionsupporting
confidence: 90%
“…Multivariate assessment also revealed that preoperative stent was not the independent predictor of stone-free rate after fURS in our study which was similar with a previous study (Ito et al, 2015). In our opinion, once the fURS successfully arrived at renal pelvis, stone-free rate for renal calculi would be more likely affected by stone characteristics and pelvicalyceal anatomy rather than the existence of preoperative stenting according to our experience and some published data (Skolarikos et al, 2015; Jessen et al, 2014; Resorlu et al, 2012). …”
Section: Discussionmentioning
confidence: 66%
“…Which is a preferable treatment method for preserving functioning renal parenchyma [2], and this is crucial to the management of patients with solitary kidney [1]. Unfortunately, RIRS cannot be recommended as first-line treatment due to which stone-free rate (SFR) showed a negative correlation with stone size [7]. SFR after RIRS was achieved in 30% of patients with >2 cm stones and usually needed re-treatment; however, overall complication rates not related to stone sizes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Daarnaast zijn in de live-URS-groep relatief gezien meer nierstenen verwijderd dan in de routine-URS-groep. Literatuur laat zien dat het aantal complicaties over het algemeen hoger is bij URS voor nierstenen dan bij URS voor ureterstenen [11,12]. In de live-URS-groep waren bovendien meer patiënten met renale anomalieën ingedeeld dan in de routine-URS-groep.…”
Section: Discussieunclassified